2022
DOI: 10.1155/2022/2881404
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of WhatsApp and Telegram on Student Engagement: An Analysis from the Mixed-Methods Approach

Abstract: One of the most studied variables in virtual online education is engagement because it contributes to retention and academic performance. Several studies show that the didactic design of the virtual course, the role of the teacher, interactivity, interaction, time spent in the virtual environment, and the use of digital social networks increase engagement. However, there is a lack of research that compares which of the two digital social networks, WhatsApp or Telegram, promotes higher levels of engagement. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…ResearchGate enables finding the necessary information, contributing to its systematisation and evaluation for developing research activities. ResearchGate also enables the search for academic information in various formats, which is reflected in various didactic guidelines (Estrada- Molina et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ResearchGate enables finding the necessary information, contributing to its systematisation and evaluation for developing research activities. ResearchGate also enables the search for academic information in various formats, which is reflected in various didactic guidelines (Estrada- Molina et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Conferences can be held offline and online using the Google Meet, Zoom, Microsoft Teams applications. Digitisation of learning contributes to the development of autonomous learning, and provides the possibility of uninterrupted consultation (Molina, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Afzal and Abdullah [28] found that teaching using WhatsApp produced efficient results in continuing the educational process in schools. Additionally, Molina [29] states that satisfactory results are obtained with WhatsApp and Telegram activities that promote adequate levels of participation.…”
Section: Benefits Of Using Whatsapp For Online Teachingmentioning
confidence: 99%
“…Mastering these competencies allows teachers to utilize a set of skills, attitudes, and knowledge to support and enhance student learning in various digital settings, e.g., virtual learning environments, educational games, personal learning environments, and digital social networks, amongst others. This requires the integration of pedagogical disciplinary knowledge, technological disciplinary knowledge, and technological pedagogical knowledge (Estrada-Molina, 2022;Skantz-Åberg et al, 2022).…”
Section: Introductionmentioning
confidence: 99%